2021
DOI: 10.1016/j.chest.2020.08.2081
|View full text |Cite
|
Sign up to set email alerts
|

Using Geospatial Analysis to Evaluate Access to Lung Cancer Screening in the United States

Abstract: BACKGROUND: Screening current and former heavy smokers 55 to 80 years of age for lung cancer (LC) with low-dose chest CT scanning has been recommended by the United States Preventive Services Task Force since 2013. Although the number of screening facilities in the United States has increased, screening uptake has been slow. RESEARCH QUESTION: To what extent is geographic access to screening facilities a barrier for screening uptake nationally? STUDY DESIGN AND METHODS: Screening facilities were defined as Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…As expected, Figure 2 shows more people have access as the distance to facilities increases, with almost 70% access at 10 miles to more than 99% access at 100 miles. In agreement with the previous report, 12 approximately 5% of the population does not have access at 40 miles. Overall, 5.1% of the eligible population does not reside within 40 miles of a facility, and this proportion is markedly higher among individuals living in micropolitan and rural counties at 17.1% and 24.5%, respectively.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As expected, Figure 2 shows more people have access as the distance to facilities increases, with almost 70% access at 10 miles to more than 99% access at 100 miles. In agreement with the previous report, 12 approximately 5% of the population does not have access at 40 miles. Overall, 5.1% of the eligible population does not reside within 40 miles of a facility, and this proportion is markedly higher among individuals living in micropolitan and rural counties at 17.1% and 24.5%, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Geospatial analysis is often used to calculate proximity, assess the availability of health services, identify gaps in resources, and inform public health policies. 12,15,16 We used Esri's ArcGIS 10.6.1 (esri.com) for mapping and spatial analysis. Maps throughout this article were created using ArcGIS software by Esri.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also should be obvious that a favorable ratio of supply and demand can change; if unnoticed, shrinking demand in the presence of declining access will adversely affect disease control efforts. Sahar et al 9 found that nationwide, <6% of people 55 to 79 years old in the United States did not have access to low-dose CT screening based on 40-mile road distance and identified local disparities. Eberth et al 10 reported an average of 14.9% across all states of people 55 to 79 years old who did not have access within 30-mile Euclidean distance and indicated disparity in distribution of facilities across rural-urban areas.…”
mentioning
confidence: 99%
“…Although visual interpretation can be very informative for policy-makers and a catalyst for action, future analyses can benefit from using quantitative spatial analysis at a more granular geographic level and integrating datasets such as mortality and incidence rates to further identify local gaps in services and refine measures of "need." 9 The VHA is a unique national health system that can coordinate services that include quality lung cancer screening across regions. Not only do the results depicted in this article provide valuable information that can assist in program planning and resource allocation, but they also can provide insight into disparities, barriers, and practices that contribute to low lung cancer screening uptake so that these factors can be addressed and overcome.…”
mentioning
confidence: 99%